ChemInform Abstract: Hybrid Energy Storage: The Merging of Battery and Supercapacitor Chemistries. Issue 22 (15th May 2015) - Dubal, D. P.; Ayyad, O.; Ruiz, V.; Gomez‐Romero, P.
Abstract: Review: 50 refs.